Exploring the Relation between Farmer Group Membership and Agricultural Productivity: Evidence from Indonesian Rice Farming - Lukman Mohammad Baga; Anisa Dwi Utami; Ach Firman Wahyudi (Universitas Muhammadiyah Yogyakarta, 2023)
Farmer groups have been critical in pursuing agricultural development, particularly in developing countries. Indonesia’s government has promoted the development of farmer groups in recent years, mainly in the rice sector, as a strategic agricultural commodity. This paper explored the relations between farmer group membership, farming practices, and productivity in the Indonesian rice sector. Propensity Score Matching (PSM) and regression analysis were employed to examine the 2014 National Agricultural Survey data. The empirical findings confirmed the positive relations between farmer group membership and productivity in the Indonesian rice sector. Furthermore, farmers’ characteristics covering age, gender, education level, and farming practices, such as land status and access to irrigation, all played a role in determining the extent to which farmers participated in farmer groups.